ASSISTANCE FOR TODDLER STUNTING CASES IN SUMBER HAMLET, MINGGIR SUBDISTRICT, SLEMAN REGENCY, YOGYAKARTA - Rosmita Nuzuliana,; Safira Nurul Aini,; Ahmad Fadhil. H. ,; Muhammad Ramdani Syam Al’Am’Yubi,; Dewi Purwati, (Jurnal Cakrawala Ilmiah, 2023)
Background: In Minggir Sub-district, Pedukuhan Sumber, there is 1 stunting toddler who has not been successfully overcome. This is due to the stagnation of toddler weight and toddler height which is arguably below -2 SD in the TB / U graph. Objective: To analyze the main causes of An. Z was "stunted". Methods: This study used an intensive mentoring approach for 4 meetings. Assistance activities carried out, namely in-depth interviews with patient parents on the first day, then observations using secondary data obtained from the patient's MCH book. By asking for consent at the beginning of the meeting and taking anthropometric measurements of toddlers on the second day to be recapitulated in the TB/U, BB/U, TB/BB charts. On the third day, a child's growth and development examination is carried out using the Denver II sheet, and on the fourth day determining the core problem, problem solving and problem evaluation. Results: An. Z is classified as a "stunted toddler" not "stunting" because in the BB / TB graph An. Z is in the "Good Nutrition" category and in the results of the Denver II growth and development test, there is no delay in any aspect. In other words, the short stature of An. Z's stature is influenced by the height of her biological mother. Which, An. Z's biological mother is < 150 cm tall. Conclusion: An. Z is genetically influenced by the short stature of her biological mother who is <150 cm tall.